Techno-nature on Graham Island, Haida Gwaii - Ivakhiv, Adrian (UnderCurrents: Journal of Critical Environmental Studies, 1996)
I came to these islands at the edge of the world looking for nature, pure and pristine. Before me a century of settlers had come, bringing with them first plows (which they left and abandoned), then cars (which they left and abandoned). (Some of those cars still drive, but when word gets around that a police cruiser is visiting from the mainland, the more beat-up jalopies, unlicensed & uninsured, hide out until the roads are safe for them again.) I came armed with notebook, to do research. Instead I sunk into the moss, the dense, misty wetness of the earth. Like these cars, excess and refuse of industrial civilization, driven as far as they could go, then left stranded, refugees, on these islands, to be reclaimed by nature.